Bioengineering in wound healing a systems approach - Yarmush, Martin L.; Golberg, Alexander (Frontiers in nanobiomedical research, 2017)
What is a wound, how does it heal, and how can we prevent scarring? The concept of wound healing has puzzled humans even before the advent of modern medicine. In recent years, bioengineering has tackled the problems of cancer, tissue engineering and molecular manufacturing. The broad spectrum of technologies developed in these fields could potentially transform the wound care practice. However, entering the world of wound healing research is challenging -- a broad spectrum of knowledge is required to understand wounds and improve healing. This book provides an essential introduction of the field of wound healing to bioengineers and scientists outside the field of medicine. Written by leading researchers from various fields, this book is a comprehensive primer that gives readers a holistic understanding of the field of wound biology, diagnostics and treatment technologies."--Publisher's website